Urban popular movements: an interpretive framework - Pinheiro, Jair (Pontifícia Universidade Católica de São Paulo, 2011)
This article is a theoretical reflection on thecategories of subject and structure in light ofthe empirical observations of research I havebeen conducting on popular movements in thecity of São Paulo. The objective is to criticizethe assumption that this debate is no longerrelevant. Thus, I try to formulate four theses thatmediate between the two categories, since thetheoretical assumption is that structures do notimpede action, on the contrary, they make actionpossible and, at the same time, action transformsstructures, in accordance with the specific aspectsof each structure (economic, legal-political andsociocultural) in the capitalist mode of production.